Assessing health-related quality of life in COPD: comparing generic and disease-specific instruments with focus on comorbidities - Wacker, Margarethe E. (BMC Pulm Med, 2016)
BACKGROUND: Chronic Obstructive Pulmonary Disease (COPD) influences different aspects of patient’s health-related quality of life (HRQL). While disease-specific HRQL instruments focus on symptoms and functional impairments, generic instruments cover a broader view on health. This study compares the generic EQ-5D-3 L and two disease-specific questionnaires (St.-George’s Respiratory Questionnaire (SGRQ-C), COPD Assessment Test (CAT)) in a comprehensive spectrum of COPD disease grades with particular attention on comorbidities and assesses the discriminative abilities of these instruments. METHODS: Using data from the baseline visit of the German COPD cohort COSYCONET, mean HRQL scores in different COPD grades were compared by linear regression models adjusting for age, sex, education, smoking status, BMI, and low vs. high number of comorbidities or a list of several self-reported comorbid conditions. Discriminative abilities of HRQL instruments to differentiate between COPD grades were assessed by standardized mean differences. RESULTS: In 2,291 subjects in COPD GOLD grades 1–4 EQ-5D-3 L utility, EQ-5D VAS, SGRQ, and CAT were found able to discriminate between COPD grades, with some limitations for the EQ-5D utility in mild disease. Both generic and disease-specific HRQL instruments reflected the burden of comorbid conditions. The SGRQ showed the best discrimination between COPD grades and was less influenced by comorbidities, while EQ-5D utility put a higher weight on comorbid conditions. For all instruments, psychiatric disorders and peripheral artery disease showed the strongest negative associations with HRQL. CONCLUSION: All HRQL instruments considered reflect considerable impairment of HRQL in COPD patients, worsening with increasing COPD grade and number of comorbidities. Findings may support clinical assessment, choice of HRQL instrument in future studies, and parameterization of decision-analytic models. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12890-016-0238-9) contains supplementary material, which is available to authorized users.